Comparative effects of low-load blood flow restriction training and high-load resistance training on physical performance in college 800-m runners: a randomized control trial - Yu, J.; Yu, J.; Zhao, L.; Yang, Y. (Frontiers in Physiology, 2025)
Background: High-load resistance training (HLRT) is commonly used to enhance performance in 800-m runners but may not always be suitable. Low-load blood flow restriction (BFR) training offers similar benefits to HLRT while reducing these issues. This study aimed to compare the effects of traditional HL-RT and low-load BFR training on muscular strength, power, endurance, and running performance of collegiate 800-m runners over an 8-week training program.